2022
DOI: 10.1159/000526945
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lifestyle and Educational Bridging Programs before Bariatric Surgery on Postoperative Weight Loss: A Systematic Review and Meta-Analysis

Abstract: Objective: To fulfill the requirements for bariatric surgery, patients often need to participate in mandatory pre-operative lifestyle interventions (PLI). Currently, the efficacy of multi-month PLI-programs on body mass index (BMI) reduction from the start of the program (T0) through the immediate pre-operative time point (T1) to one-year post-surgery (T2), and how the amount of pre-operative BMI reduction affects post-operative outcome (T1 to T2) is unclear. The aim of this meta-analysis was to analyze the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 58 publications
2
0
0
Order By: Relevance
“…However, there was no significant difference between the two groups at each stage, suggesting that the PEP had little impact on weight loss achieved at the time of surgery and at 2‐year follow‐up. Similar results were achieved in a recent meta‐analysis analyzing four studies, which indicated that preoperative lifestyle programs did not significantly impact on weight loss after 1‐year post‐surgery 19 . This study also found that both groups achieved significant improvements in glycemic control from initial enrollment to pre‐surgery.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…However, there was no significant difference between the two groups at each stage, suggesting that the PEP had little impact on weight loss achieved at the time of surgery and at 2‐year follow‐up. Similar results were achieved in a recent meta‐analysis analyzing four studies, which indicated that preoperative lifestyle programs did not significantly impact on weight loss after 1‐year post‐surgery 19 . This study also found that both groups achieved significant improvements in glycemic control from initial enrollment to pre‐surgery.…”
Section: Discussionsupporting
confidence: 87%
“…Similar results were achieved in a recent meta-analysis analyzing four studies, which indicated that preoperative lifestyle programs did not significantly impact on weight loss after 1-year post-surgery. 19 This study also found that both groups achieved significant improvements in glycemic control from initial enrollment to pre-surgery. Tight glycemic control preoperatively has been associated with reduced perioperative morbidity and mortality.…”
Section: Discussionsupporting
confidence: 55%